Determining p-values for Systems Cointegration Tests With a Prior Adjustment for Deterministic Terms - Carsten Trenkler (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
In this paper I present a procedure to approximate the asymptotic distributions of systems cointegration tests with a prior adjustment for deterministic terms suggested by Lütkepohl, Saikkonen & Trenkler (2004), Saikkonen & Lütkepohl (2000a, 2000b, 2000c), and Saikkonen & Luukkonen (1997). The asymptotic distributions are approximated by the Gamma distribution and the parameters necessary to fit the Gamma distributions are obtained from response surfaces which I describe in this paper. The approximation can be easily used to derive arbitrary p-values or percentiles.
Keywords: C15; 330; p-values; systems cointegration tests; response surface